The king Abi-sare his rule and descent - abed, Basima; alwash, huda (مجلة دراسات في التاريخ والآثار, 2020)
He is the sixth king of the kings of larsa, came power after the king Gungunum, the sources and Sumerian kings list mention that he ruled 11 years(1) (1895-1905),but if we follow his date formulas, we will find more than 11 years, in addition to the state of ambiguity in its descents it is true that its mentioned in the list of kings that it comes after the king Gungunum ,but we have no information about the connection that binds them , so in this research we clarify some of the things related to the descents and duration of his rule through new cuneiform studies and unpublished cuneiform Text .